TEKNIK PEMBESARAN IKAN NILA (Oreochromis niloticus) SISTEM AKUAPONIK DI OPO Q FARM CACABAN, KOTA MAGELANG, PROVINSI JAWA TENGAH - Ayu Rizki Amalia; Taufik Hadi Ramli; Ayu Dea Restiana; Hermawan Gatot Priyadi; Agung Doni Anggoro; Purwanto Purwanto (Jurnal Perikanan Pantura (JPP), 2024)
Tilapia, also known as Oreochromis niloticus, is an important commodity in Indonesia that contributes to national food security, economic sustainability and community welfare. The aim of this research is to determine techniques for rearing tilapia cultivation using an aquaponic system. The aquaponics system uses water from fish farming ponds which is channeled through pipes for cultivating plants. This research uses an observation and active participation methodology, namely going directly to the field during tilapia (Oreochromis niloticus) rearing activities using an aquaponic system at OPO Q Farm Cacaban, Magelang City. The research results show that the aquaponics system is an effective method for cultivating tilapia. The process includes preparing the tilapia cultivation container, lettuce plant container, sowing the lettuce plants, stocking the fish, filling the lettuce seeds into the netpot container, providing food, and checking the water quality. The aquaponics system produced a high FCR of 1.06 tilapia, a survival rate of 99%, and a lettuce yield of 47.5 kg. The water quality of the aquaponic system is considered ideal, with temperatures ranging from 23-26°C, pH 6.5-7.5, DO 5.74-6.76 mg/L, and Ammonia 0 ppm. Lettuce plants effectively absorb food and fish metabolic waste, thereby ensuring that the water quality in the aquaponic tilapia cultivation medium is maintained.